2011
DOI: 10.1523/jneurosci.5492-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens μ-Opioid Receptors Mediate Social Reward

Abstract: Positive social interactions are essential for emotional well-being and proper behavioral development of young individuals. Here, we studied the neural underpinnings of social reward, by investigating the involvement of opioid neurotransmission in the nucleus accumbens (NAc) in social play behavior, a highly rewarding social interaction in adolescent rats. Intra-NAc infusion of morphine (0.05–0.1 μg) increased pinning and pouncing, characteristic elements of social play behavior in rats, and blockade of NAc op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(244 citation statements)
references
References 69 publications
14
229
0
1
Order By: Relevance
“…It is not surprising that peripheral blockade of -opioid receptors failed to inhibit selective aggression since previous studies have demonstrated that blockade of these receptors is aversive (van Ree et al, 1999;Kenny et al, 2006;Le Merrer et al, 2009). In contrast to negative affective states induced by -opioid-receptor blockade, activation of these receptors is associated with positive hedonics and mediates the rewarding properties of positive social incentives such as play and contact comfort (Panksepp et al, 1980;Vanderschuren et al, 1995;Trezza et al, 2011). Moreover, activation of -opioid receptors is important for the early stages of pair bond formation, as blockade of these receptors within the striatum inhibits the formation of a partner preference (Burkett et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that peripheral blockade of -opioid receptors failed to inhibit selective aggression since previous studies have demonstrated that blockade of these receptors is aversive (van Ree et al, 1999;Kenny et al, 2006;Le Merrer et al, 2009). In contrast to negative affective states induced by -opioid-receptor blockade, activation of these receptors is associated with positive hedonics and mediates the rewarding properties of positive social incentives such as play and contact comfort (Panksepp et al, 1980;Vanderschuren et al, 1995;Trezza et al, 2011). Moreover, activation of -opioid receptors is important for the early stages of pair bond formation, as blockade of these receptors within the striatum inhibits the formation of a partner preference (Burkett et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is studied in the lab using tests of selective aggression toward unfamiliar conspecifics (Gavish et al, 1983;Winslow et al, 1993;Young et al, 1997), and it is known that this behavior is regulated by D 1 -like receptors within the NAc shell (Aragona et al, 2006). Thus, D 1 -and D 2 -like receptors within the NAc shell-a region important for processing social incentives (Li and Fleming, 2003;Champagne et al, 2004;Trezza et al, 2011)-exert differential regulation over the formation and maintenance of monogamous pair bonds (Aragona et al, 2006). Differential regulation over pair bonding by D 1 -and D 2 -like receptors is significant because these receptors are primarily expressed on distinct neuron populations (Le Moine and Bloch, 1995;Perreault et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Encounter stimulation increased c-Fos expression in the nucleus accumbens shell of group-and isolationreared mice to a similar degree. Activation of nucleus accumbens increases exploratory and social play behaviors in rats (Falowski et al, 2011;Trezza et al, 2011;van Kuyck et al, 2007). Thus, enhanced neuronal activity in the nucleus accumbens shell may contribute to social interactions in male group-and isolation-reared mice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated the possible co-occurrence of adult play and stereotypic behaviors in captive rhesus and long-tailed macaques living under intensive husbandry conditions (see above). There are reasons to believe that the two categories of behaviors may be related: they are both quasi absent of the repertoire of these species in natural conditions and they are both related to the release of endogenous opioids and to basal ganglia and striatum brain structures (Graham, 2011;Normansell & Panksepp, 1990;Pellis & McKenna, 1992;Trezza et al, 2010;Trezza, Damsteegt, Achterberg, & Vanderschuren, 2011).…”
Section: Stereotypic Behavior and Adult Play: A Co-occurrence In Primmentioning
confidence: 99%
“…There is no doubt that, at the precise time of play, animals (like humans) experience positive emotions, as play involves neurotransmitter systems that are also involved in the hedonic properties of food and drug rewards (opioids, cannabinoids and dopamine) (Trezza et al, 2011). It has been shown that opioids modulate social play by influencing its subjective positive properties (Trezza et al, 2010).These same systems are however also involved in compulsive games in humans (Frost, Steketee, & Green, 2003) and wheel running in rodents (Sherwin, 1998).…”
Section: Adult Play As An Indicator Of Welfare?mentioning
confidence: 99%